Alcohol consumption among older adults: Findings from the ELSI‐Brazil study - Paula, Tassiane C. S.; Chagas, Camila; Henrique, Amanda E. G.; Castro‐Costa, Erico; Lima‐Costa, Maria Fernanda; Ferri, Cleusa P. (International journal of geriatric psychiatry, 2022)
Objectives This study estimates the national prevalence of drinking patterns (current, heavy, and binge) and the associated factors, among older Brazilians. Design Cross‐sectional study using survey data from ELSI‐Brazil (2015–2016). Setting/Participants A total of 7839 adults aged 50 years or older. Measurements Respondents were asked about alcohol drinking. Alcohol consumption status was categorized as current drinkers (last month), heavy drinkers (≥7 drinks/week for females and ≥14 drinks/week for males), and binge drinkers (≥4 drinks on one occasion for females and ≥5 drinks on one occasion for males). Covariates included sociodemographic characteristics, tobacco smoking, depression, and number of chronic diseases. Results Of the 7839 participants, 29.4% were current drinkers, 5.1% were heavy drinkers, and 10.3% reported binge drinking. In the ≥60 years old age group, the prevalence of current drinking was 23.8%, 3.9% were heavy drinkers, and 6.7% reported binge drinking. All drinking patterns had similar associated factors: being male, being younger, having higher education, tobacco smoking, and falls. In addition, the greater the number of chronic conditions, the lower the prevalence of current drinking and binge drinking. Conclusion Heavy drinking and binge drinking are often reported by older Brazilians, particularly among males, those with higher education and in the younger age groups. These behaviors can negatively affect the health of older adults. It is, therefore, important to identify the problems related to alcohol consumption among older adults to minimize the risks and harms. Key points A national representative study in Brazil found that 29.1% of adults (41.1% male and 18.9% female) aged over 50 were current drinkers, and this is lower in adults (23.7%: 35.9% male and 14% female) aged over 60. The prevalence of current heavy drinking among those aged 50 and over was 5.1% and 3.9% among those 60 and over. The prevalence of current binge drinking among those aged 50 and over was 10.3% and 6.7% among those 60 and over. Younger males, those with higher education and tobacco smokers were more likely to be heavy and binge drinkers.